MOBILE APPLICATION FOR ZAKAT, INFAK, AND SADAQAH BASED ON SHARIA ECONOMICS - Siti Alwya Syarif (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
The research method used in this study is a qualitative approach with a case study method. The primary goal is to deeply understand the experiences and perceptions of users towards a mobile application designed for the management of zakat, infak, and sadaqah based on Sharia economics. Primary data were collected through a series of in-depth interviews with users of the application and zakat managers at various Islamic financial institutions. Respondents were selected using purposive sampling techniques to obtain a rich variety of perspectives from individuals who have direct experience with the application. Additionally, document analysis was conducted to gather secondary data including promotional materials for the application, financial reports of zakat institutions, and online publications related to the use of technology in the distribution of zakat and sadaqah. Data analysis was performed using thematic coding techniques, where collected data were organized and analyzed to identify major themes and emerging patterns. This study emphasizes strict research ethics by ensuring the confidentiality and anonymity of all respondents. The results of this study are expected to provide valuable insights regarding the effectiveness and impact of using mobile applications to enhance the practices of zakat, infak, and sadaqah among the Muslim community.